ANALISIS PENERAPAN SISTEM KLASIFIKASI KHUSUS DI PERPUSTAKAAN IAIN FATTAHUL MULUK PAPUA - Zulihi, Zulihi; Tuwaji, Tuwaji; Kahfi, Sahibul (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2024)
(Objectives) The organisation of library materials in a library is very important. For this reason, it is important to choose the right classification system with the aim of making the collection more useful for users. IAIN Fattahul Muluk Papua Library applies a special classification system developed by the library itself.  (Method) Therefore, the author has an interest in studying this system using a descriptive method with a qualitative approach with data collection methods using interviews, observations, documentation, and literature studies. (Findings) The results obtained are 1) this classification uses the main basic subjects namely tarbiyah, sharia, muamalah, and general popular subjects. For other than monographs, the classification is based on form and presentation. For notation using letter and number notation. 2) There are several advantages including simple subjects and notations and information retrieval is relatively easy. The disadvantages are that the classification is not yet universal, the division of knowledge is not detailed, not systematic, the classification is not flexible, does not have an index, does not have a supervisory body. In addition, there are problems including inconsistency in classification, overlapping titles in the database, ineffective and inefficient information retrieval, non-mechanised collection preparation.